The impact of the recent migration from Eastern Europe on the UK economy - David Blanchflower; Jumana Saleheen; Chris Shadforth (Bank of England, External Monetary Policy Committee Unit, 2007)
The recent rise in migration to the UK from eight EU Accession countries (the Czech Republic; Estonia; Hungary; Latvia; Lithuania; Poland; Slovakia; and Slovenia - the A8 countries) has generated a good deal of controversy. How many A8 immigrants are there in the UK? Where did they come from and when? What impact has their influx had on the UK economy and what likely impacts will they have in the future? Most importantly for the Monetary Policy Committee (MPC), what macroeconomic effects have they had? We attempt to address these questions here. First, we examine the change in population in the UK over the last thirty-five years and note that growth is very low by international standards. The UK population has, however, grown at a faster pace since the turn of the millennium, driven most recently by migration from the A8 nations. It appears that the propensity to migrate to the UK from these countries is higher the lower is GDP per capita. Second, we examine the various sources of data that are available on the numbers of A8 immigrants that have arrived in the UK in recent years. There is broad agreement from the various data sources on the numbers involved - half a million workers is likely to be an upper bound for the stock of A8 migrants who are in the UK in late 2006. Many of the new 'migrants' may have stayed for only a short time and then returned home, to possibly return again at a later date. Third, we examine the characteristics of the recent flow of individuals from the A8 countries that have arrived in the UK since accession, and find that they are relatively young, male, have low unemployment rates, lower wages, and high self-employment rates and are especially likely to be in temporary jobs. Finally, we turn to the macroeconomic implications of A8 migration to the UK, and argue that this immigration has made the labour market more flexible and likely lowered the natural rate of unemployment and the NAIRU.
Keywords: 330; Einwanderung; Osteuropäer; Internationale Arbeitsmobilität; Makroökonomischer Einfluss; Preisniveaustabilität; Natürliche Arbeitslosigkeit; Großbritannien